Pharmacological management of modifiable cardiovascular risk factors (blood pressure and lipids) following diagnosis of myocardial infarction, stroke and diabetes: Comparison between population-based studies in Russia and Norway - Cook, Sarah Anne; Hopstock, Laila Arnesdatter; Eggen, Anne Elise; Bates, Katie; Iakunchykova, Olena; Kontsevaya, Anna; McKee, Martin; Schirmer, Henrik; Voevoda, Michael; Kudryavtsev, Alexander V; Malyutina, Sofia; Leon, David A. (BMC Cardiovascular Disorders, 2020)
Background - Cardiovascular disease (CVD) mortality is substantially higher in Russia than in neighbouring Norway. We aimed to compare blood pressure- and lipid-lowering medication use and proportion meeting treatment targets between general population samples in the two countries in those with CVD and diabetes. Methods - The study population was adults aged 40–69 years reporting a diagnosis of myocardial infarction (MI), stroke and/or diabetes participating in cross-sectional population-based studies in Russia (Know Your Heart (KYH) 2015–18 N = 626) and Norway (The Tromsø Study 2015–16 (Tromsø 7) N = 1353). Reported medications were coded according to the 2016 WHO Anatomical Therapeutic Chemical Classification system. Treatment targets were defined using the Joint European Societies guidelines for CVD prevention in clinical practice (2016). Results - Age- and sex-standardized prevalence of use of lipid-lowering medications was higher in Tromsø 7 for all three conditions with a disproportionately large difference in those reporting MI (+ 48% (95% CI 39, 57%)). Proportion meeting treatment targets for LDL cholesterol was poor in both studies (age- and sex-standardized prevalence of control KYH vs Tromsø 7: MI 5.1% vs 10.1%; stroke 11.6% vs 5.8%; diabetes 24.9% vs 23.3%). Use of antihypertensive medication was higher in KYH for stroke (+ 40% (95% CI 30, 50%)) and diabetes (+ 27% (95% CI 19, 34%)) groups but approximately equal for the MI group (− 1% (95% CI -1, 1%)). Proportion meeting blood pressure targets was lower in KYH vs Tromsø 7 (MI 51.8% vs 76.3%; stroke 49.5% vs 69.6%; diabetes 51.9% vs 63.9%). Conclusions - We identified different patterns of medication use in people with CVD and diabetes. However despite higher use of lipid-lowering medication in the Norwegian study treatment to target for total cholesterol was poor in both Russian and Norwegian studies. In contrast we found higher levels of use of antihypertensive medications in the Russian study but also that less participants met treatment targets ...